Salmonella - A Re-Emerging Pathogen 2018
DOI: 10.5772/intechopen.77210
|View full text |Cite
|
Sign up to set email alerts
|

Virulence System of <i>Salmonella</i> with Special Reference to <i>Salmonella enterica</i>

Abstract: Virulence system of Salmonella is very complex as many genes are involved in contributing the virulence of Salmonella. Some of the genes are involved in enhancing the invasion of organism in host defense system; some are playing their role in survival and replication of organism inside the host, while some genes are involved in the production of molecules that produce the clinical symptoms of the disease. Broadly, we can classify virulence genes into two categories: genes that are located on the virulence cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 37 publications
(37 reference statements)
0
24
0
Order By: Relevance
“…There are a total of 17 SPI described in Salmonella [22]. SPI-1 to SPI-5 have been widely characterized and can be found in most S. enterica .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are a total of 17 SPI described in Salmonella [22]. SPI-1 to SPI-5 have been widely characterized and can be found in most S. enterica .…”
Section: Resultsmentioning
confidence: 99%
“…While the genes that make up each SPI are not known whether all serovars have the same SPI constituent gene. In S. Typhimurium [23] and S. Typhi [22], the SPI-1 to SPI-5 genes have been wholly identified. Amavisit et al [24] reported that there were genetic variations between SPI-1, SPI-3, and SPI-5, while the genetic variation of SPI-4 and SPI-2 was not easily changed among 13 Salmonella serovars isolated from cattle, pigs, poultry, horses, environment, and humans [24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural proteins are responsible for the assembly of the T3SS apparatus, formed by two rings crossing the inner and outer bacterial membrane, linked to a needle-like system that pierces the host cellular membrane [10,11]. The latter structure is crucial for the transport of the effector proteins, delivered by translocators from the bacterial cell into the host: here, effectors manage fundamental changes enabling key steps for Salmonella pathogenesis [12]. During the bacterial infection, Salmonella invade the enterocyte and survive into the host cytoplasm surrounded by large vesicles, called Salmonella-containing vacuoles (SCV) [13].…”
Section: Introductionmentioning
confidence: 99%
“…125,126 Another effector that mediates apoptosis in epithelial cells is SrfT, which is encoded in SPI-2. 127 Moreover, SrfH mediates actin remodeling and is located in prophage. SrfD, SrfE, SdrI, SrfK, SrfL, and SrfM also are encoded by Phage.…”
Section: Salmonella Toxins Cytotoxinmentioning
confidence: 99%